Factors of formation of organizational culture of modern logistics enterprises: general and special - Melnyk, Alla; Polynyak, Volodymyr (Herald of Economics, 2023)
Introduction. The changes that occurred in the global and national economic environments led to increased attention to the activities of logistics enterprises, increased competition in the logistics services market, the need to enhance the economic efficiency of their activities and competitiveness, which are largely determined by the quality of management and, first of all, the type and level of organizational cultures of these enterprises. In its formation, an objective and comprehensive diagnosis of factors influencing the choice of a model of organizational culture, methodological approaches to its construction, considering the type of goals and tasks of modern logistics enterprises, is of decisive importance, which determines the need for the development of a modern theoretical and methodological platform for their solution.Purpose – the development of theoretical and methodological basis of the formation of the organizational culture of enterprises and organizations and the development of proposals regarding the analysis of factors that affect this and must be taken into account in the activities of logistics enterprises in the conditions of modern challenges.Methods. The research is based on a systems approach, including a set of the following methods: analysis and synthesis, systematization, expert evaluation of the internal and external environment of the organization, PEST analysis, comparative analysis.Results. On the basis of the analysis of theoretical investigations of domestic and foreign scientists regarding the problem of the organizational culture of enterprises and the factors affecting its formation, we put forward and substantiated the hypothesis about the expediency of considering the research problem through a combination of general and special, taking into account the specifics of the activities of various types of organizations, the content of their work, which is important for strategic and situational management. Methodical approaches to (selection of a criterion base) classification of factors for the formation of the organizational culture of enterprises are generalized and supplemented with factors that express the specificity of their functional activity. The activities of various types of logistics enterprises in the conditions of modern challenges are analyzed (the spread of the COVID-19 pandemic, military actions of the Russian Federation on the territory of Ukraine, problems related to the destruction of the energy system of Ukraine and transport infrastructure, trends towards the decline of economic dynamics in the world, etc.). There is a well-founded need to update analytical diagnostics taking into account changes in the external environment of logistics enterprises, focusing on strengthening the factors of increasing competitive advantages and competitiveness of these enterprises.Discussions. Further scientific research should be focused on the empirical analysis of the practice of forming the organizational culture of various types of logistics enterprises, the peculiarities of their organizational culture’s adaptation to digitalization and remote work.